ASSOCIATION PATTERN AND REGRESSION ANALYSIS FOR YIELD AND ITS ATTRIBUTING TRAITS IN SAFFLOWER (Carthamus tinctorius L.) - P.S. SRINIVAS and P. RATNAKUMAR, K. DIVYA1 , V. HEMALATHA , KADIRVEL PALCHAMY , V. DINESH KUMAR (The Journal of Research, PJTSAU, 2023)
The present study was conducted to determine the interrelation among yield and its related traits in safflower using a RIL population derived from the cross between CO-1 and EC-523368-2. The RILs were phenotyped for seven traits, days to 50% lowering, days to maturity, plant height, number of primary capitula/plant, number of seeds/primary capitulum, 100 seed weightand seed yield. Trait mean in the population was observed as 82.08 days for days to 50% flowering, 112.15 days for days to maturity, 75.62 cm for plant height, 6.71 primary capitula/ plant, 28.96 seeds/ primary capitulum, 3.29 g for 100 seed weight. Meanof seed yield was observed as 9.44 ranging from 1.99 to 34.38 g. Correlation analysis revealed the strong positive correlation ofseed yield with number of seeds/ primary capitulum, number of primary capitula/ plant, plant height and 100 seed weight. Thestepwise regression analysis explained 47% of variation for seed yield (coefficient of determination R2=0.47) and adj. R2 as 0.45and developed a best fit linear regression equation as, SY = -9.55 + 0.06PH + 0.77NPCP + 0.21NSP + 1.06HSW. Based on Mallows’ Cp (low- 4.18), R2 (high- 87.45) and adj. R2 (high-87.01), the best fit regression model from all possible models was PH + NPCP + NSP + HSW. Selection for these traits may help to improve the seed yield potential in safflower.